Analisis Pengaruh PDRB, UMP, Investasi, Pengangguran dan Pandemi Covid-19 Terhadap Tingkat Kemiskinan di Indonesia: Studi Data Panel 2015-2023 - Alfina Putri Satyatama (Universitas 45 Surabaya, 2025)
Poverty is a multi-layered and complex economic problem in Indonesia. This study aims to explore the factors that influence the poverty rate in 34 Indonesian provinces in the period from 2015 to 2023 by utilizing the static panel regression method. The independent variables analyzed include Gross Regional Domestic Product (GRDP), Provincial Minimum Wage (UMP), investment, and the open unemployment rate. Secondary data was collected from the Central Statistics Agency (BPS) and other relevant sources. The findings of this study show that GRDP and investment have a negative and significant impact on the poverty rate, indicating that economic growth and increased investment can serve to reduce poverty rates. In contrast, the open unemployment rate shows a positive relationship with poverty, indicating that increased unemployment worsens the poverty situation. Meanwhile, the results of the minimum wage vary in different provinces, depending on the dynamics of the labor market and local economic policies. The implications of this study emphasize the importance of developing policies that support inclusive economic growth, increasing investment that has a direct impact on job creation, and strategies to reduce unemployment rates to tackle poverty more effectively.